Performance management system:evolution and re-evaluation - Mohd Alwi, Norhayati; Abdul Khalid, Siti Nabiha (Trisakti University, 2006)
Business organisations are constantly faced with external and internal forces that drive them to change. These changes have had various impacts on the use of performance management system. With the new way of doing business, the information derived from traditional management control systems is claimed to be too aggregated, too late and too distorted and it could no longer be an effective mechanism to govern an organisation (Johnson & Kaplan, 1987). Thus, various new performance management system and framework (PMS) such as balanced scorecard, linked structure model and economic value added, have been advocated and claimed to be able to address the needs of contemporary organisations. Thus in this paper, a review of the development of performance management system and evaluation of the efficacy of both the traditional and contemporary performance systems are undertaken. Criticisms of the traditional functional measures that arise in the mid 1980s which lead to the introduction of several prominent performance management frameworks are discussed. The paper continues with re-evaluation on the contemporary performance measurement frameworks with the objectives of ascertaining their applicability to replace or to supplement the traditional performance measures. Finally, discussion on critical issues related to performance management that might require reformations are addressed in the final section of this paper.